Barriers to treatment for opioid use disorder in Colombia. (2nd November 2021) - Borda, Juan P.; Friedman, Hannah; Buitrago, Jhon; Isaza, Maritza; Herrera, Paula; Krawczyk, Noa; Tofighi, Babak
ABSTRACT: Background: In Colombia, the rapid rise of illicit opioid use has become a major public health concern. Medications for opioid use disorder (MOUD) are well established and effective. However, access to MOUD remains suboptimal in this country. This paper aims to understand barriers to accessing MOUD in Colombia to inform the integration of this treatment modality in health systems. Methods: This study is a cross-sectional survey among persons with opioid use disorder (OUD) not enrolled in MMT in four Colombian cities with high known OUD prevalence. Survey domains consisted of the Barriers to Treatment Inventory, attitudes pertaining to MOUD treatments, and perceptions regarding interventions to ease access to Methadone. Results: A total of 84 subjects completed the survey. The most commonly endorsed barriers were related to admission difficulties, including concerns with "too many steps to get into treatment" (84.3%), experiencing withdrawal symptoms (78.1%), being placed on waiting lists (48.2%), and cost (44.6%). Nearly all participants were receptive to Methadone dispensation in primary care (96.4%) or mobile vans (91.6%). Conclusions: Findings from this study highlight persistent barriers to linking with MOUD among adults with OUD in Colombia requiring increased outpatient treatment programs, flexible methadone dosing, and administrative and financial support for patients.